APPLICATION OF Azospirillum brasilense AND NITROGEN IN TOPDRESSING IN CORN HYBRIDS (REVISTA DE AGRICULTURA NEOTROPICAL, 2023)
Corn (Zea mays L.) is the most cultivated cereal in the world. The high yields obtained for this crop are mainly linked to nitrogen requirements. Technologies that aim to reduce costs with nitrogen fertilizers, with less environmental impact, such as diazotrophic bacteria, should be considered an advantageous alternative for this crop. The present study aimed to evaluate two corn hybrids, BioGene 7046® and Dekalb 310®, with three topdressing nitrogen doses (0.35 and 70 kg ha-1 of N) associated with four application methods of Azospirillum brasilense (without inoculation, seed inoculation, foliar inoculation, and the combination of inoculation via seeds and leaves). A randomized block design with four replications arranged in a 2x3x4 factorial scheme was used to evaluate variables related to growth and development, physiological analysis of nitrate reductase enzyme activity, and yield variables and their components. The use of Azospirillum brasilense did not affect the development of corn plants and did not increase grain yield. In the edaphoclimatic conditions in which this research was developed, nitrogen fertilization at doses of 35 and 70 kg ha-1 benefit nutrition, development, and corn yield components but are insufficient to increase grain yield.